Konser Musik di Media: “Common Culture”, Anti-otentisitas dan Budaya Populer - M. Ridha al Qadri (Jurnal Komunikasi, 2008)
This article lengthens music concert phenomenon and its reproduction at media. With many perspectives of culture, music concert is reviewed in form of cultural experiences, especially about common culture, media culture, anti authenticity, and popular culture. In this article, entire trend and theoretical observation explored by find beginning references in evaluate contemporary cultural identity of popular music. In fact, the next development of music and media industries are part of complex influence culture in Indonesian society, especially from mediation of musical performance. The aims of the languages from the event, like “Free Your Voice" are integrating and representing culture of popular music.